Kísérlet a magyarországi választókerületek huszadik század eleji etnikai karakterének meghatározására - Pap, József (Közép-Európai Közlemények, 2010)
In this study we made an attempt to define the ethnic characters of the constituencies. We demonstrated the limits we come up against in the course of our work. Those statistical sources we have already processed up to now do not make it possible to form a true notion of the ratio of the national minorities in the population and in the group with property qualification, forming the local elite, in the constituencies. We attach importance to the solution of this problem from the point of view of the regional investigation of the results of parliamentary elections. We tried to remedy the shortage of sources by the help of statistical estimation. On the basis of the estimated ethnic character of the constituencies a map was constructed. As a result of our examination it was proved that the ethnic characters of the constituencies were parallel with the ethnic construction of the electors, consequently in our opinion the national minorities were not at a disadvantage in the course of the parliamentary elections. Additionally a map was made to show those constituencies where the parties of national minorities had success on the elections.